2007
DOI: 10.1109/tbme.2007.895749
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Fetal Heart Monitoring in Biomagnetic Measurements Using Adaptive Real-Time ICA

Abstract: Abstract-Electrophysiological signals of the developing fetal brain and heart can be investigated by fetal magnetoencephalography (fMEG). During such investigations, the fetal heart activity and that of the mother should be monitored continuously to provide an important indication of current well-being. Due to physical constraints of an fMEG system, it is not possible to use clinically established heart monitors for this purpose. Considering this constraint, we developed a real-time heart monitoring system for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In [6] it is already shown that PBSS outperforms other widely used blind source separation techniques, such as independent component analysis [5], in particular for the noninvasive fECG recordings that exhibit a low SNR. Therefore, this study only compares the performance of the developed PBSSa algorithm to the original PBSS technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [6] it is already shown that PBSS outperforms other widely used blind source separation techniques, such as independent component analysis [5], in particular for the noninvasive fECG recordings that exhibit a low SNR. Therefore, this study only compares the performance of the developed PBSSa algorithm to the original PBSS technique.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been proposed to exploit this spatial correlation to enhance the SNR of the fECG [4], [5], [6]. Of these techniques, [4], [5] are so called blind source separation (BSS) techniques, that require no a priori knowledge of the physiology of the fetal cardiac electrical system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main disadvantage is that the fast variations cannot be accurately modeled. Delfosse & Loubaton (1995), speech and image recognition Cardoso (1997), data communication Oja et al (1991), sensor signal processing Cvejic et al (2007) and biomedical signal processing Dun et al (2007)Waldert (2007.…”
Section: State Of the Artmentioning
confidence: 99%
“…Many efforts have been placed in studying fetal heart rate (HR) variability, in particular time and frequency domain variables that are important markers for fetal well-being [3]- [5]. Assessments of fetal HR and fetal behavior are nowadays cornerstones of clinical fetal evaluation and neurodevelopmental research.Fetal magnetocardiography (fMCG) is an excellent signal source for assessment of fetal HR, providing a precise signal that can be detected throughout the last half of pregnancy and often earlier [6]. It is generally believed that clinical fetal HR monitors based on Doppler ultrasound lack the precision required to accurately assess beat-tobeat variations.…”
mentioning
confidence: 99%